Analysis of Student Motivation in Online Learning for the Tourism and Hospitality Management Information System Course during the Covid-19 Pandemic - Dedi Joko Purnomo; Andi Hallang Lewa; Izza Ulumuddin Ahmad Asshofi (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2021)
Abstract : The global pandemic of the infectious disease COVID-19 has caused concern for all citizens of the world. Not only in the health sector, but also in other sectors, be it trade, economy, security, politics, transportation, and education. The policy of closing schools and colleges had to be taken to prevent the spread of the Coronavirus. Even though at the beginning of the pandemic, some countries are still trying to open schools as usual. However, in the end, due to the increasingly widespread pandemic, measures to close schools and universities had to be taken to save the education sector. The purpose of this study is to analyze students' online learning motivation in the Tourism and Hospitality Management Information System practice course which is usually carried out in a computer laboratory during the global pandemic of the COVID 19 infectious disease. This research will be conducted using a descriptive qualitative research design.. Positive responses from the lecture aspect, the ability of lecturers, facilities, and infrastructure also have a positive effect on student motivation in undergoing online lectures. The level of activity and motivation is high with the average percentage of student attendance in 1 semester reaching 92% and the collection of assignments is 85% . However, the limited financial ability of students so that the ability to buy devices is not sufficient and geographical conditions with minimal internet connections are the main obstacles to online lectures.